Axotomy-induced change in the properties of (S)-alpha-amino-3-hydroxy-5-methyl-4-isoxazolepropionate receptor channels in rat motoneurons - Abdrachmanova, G; Vlachová, V; Vyklický, L (Neuroscience, 2000)
Properties of (S)-alpha-amino-3-hydroxy-5-methyl-4-isoxazolepropionate (AMPA) receptor channels were studied in fluorescence-labelled control and axotomized motoneurons in spinal cord slices using a patch-clamp technique. Axotomy performed on the third postnatal day resulted in motoneuron death. Application of AMPA or kainate induced large whole-cell currents, but outside-out patches isolated from control motoneurons were either unresponsive or displayed only single-channel activity in response to rapid application of AMPA. Measurement of AMPA receptor channel openings in outside-out patches revealed multiple single-channel conductance levels: 12.2+/-1.0, 21. 9+/-1.5 and 32.6+/-3.2pS. In control motoneurons dialysed with spermine, the current-voltage relationship of responses induced by activation of AMPA receptor channels exhibited various degrees of inward rectification. The rectification index, the ratio of responses at +40 and -60mV, was used to compare the degree of inward rectification. The mean values of rectification index of responses to focal application of AMPA and AMPA receptor-mediated excitatory postsynaptic currents induced by focal electric stimulation were 0. 64+/-0.17 and 0.50+/-0.27, respectively. In axotomized motoneurons, the degree of rectification was significantly less for both responses induced by application of AMPA and for excitatory postsynaptic currents (0.91+/-0.09 and 0.95+/-0.12, respectively). Deactivation of AMPA receptors assessed from motoneuron excitatory postsynaptic currents at -70 mV was independent of postnatal age, with tau(fast)=0.88+/-0.35ms (A(fast)=78.2+/-11.8%) and tau(slow)=6. 3+/-3.2ms. In axotomized motoneurons, the decay time constants of excitatory postsynaptic currents were similar, tau(fast)=0.91+/-0. 42ms (A(fast)=85.8+/-12.6%) and tau(slow)=5.9+/-3.4ms. However, the mean amplitude of excitatory postsynaptic currents was only 43% of the amplitude recorded in control motoneurons. The results show that the current induced by activation of AMPA receptors in neonatal motoneurons is mediated by opening of both Ca(2+)-permeable and Ca(2+)-impermeable channels. As a result of axotomy, an experimental model of neurodegeneration, AMPA receptor channels in injured motoneurons destined to die become predominantly Ca(2+) impermeable. These findings suggest phenotypic control of AMPA receptor channel properties, presumably by affecting their subunit composition.
Keywords: Synaptic Transmission; Motor Neurons; kyselina alfa-amino-3-hydroxy-5-methyl-4-isoxazolpropionová; Animals, Newborn; Axotomy; Rats, Wistar; spermin; axotomie; nervus ischiadicus; AMPA receptory; Sciatic Nerve; potkani Wistar; Receptors, AMPA; novorozená zvířata; nervový přenos; krysa rodu Rattus; Excitatory Amino Acid Agonists; Animals; Spermine; zvířata; Rats; agonisté excitačních aminokyselin; Calcium Channels; motorické neurony; alpha-Amino-3-hydroxy-5-methyl-4-isoxazolepropionic Acid; vápníkové kanály